1966
DOI: 10.1126/science.154.3749.645
|View full text |Cite
|
Sign up to set email alerts
|

Maya Blue: A Clay-Organic Pigment?

Abstract: Maya Blue, a pigment used by the Mayas in Yucatan, is remarkably stable: the color is not destroyed by hot concentrated mineral acids or by heating to about 250 degrees C. The principal constituent is the colorless mineral attapulgite. It is proposed that the pigment is an adsorption complex of attapulgite and natural indigo; a synthetic equivalent may be prepared from attapulgite and either indoxylester or indigo, or by applying the vat-dyeing technique, with reduced indigo.The low dye content of the pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
166
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(180 citation statements)
references
References 3 publications
4
166
0
10
Order By: Relevance
“…9 Furthermore, it has been recently reported that mixtures of dehydroindigo and indigo are responsible for the various green-blue hues seen in ancient Mayan artifacts. 10 It is the purpose of this report to explore the binding of indigo to palygorskite at two compositions (6% wt and 16% wt) and three preparation times (3,6, and 9 h). The conversion of the mixtures of organic and palygorskite to the organic/inorganic complex occurs at 170°C in air.…”
Section: F S Manciu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…9 Furthermore, it has been recently reported that mixtures of dehydroindigo and indigo are responsible for the various green-blue hues seen in ancient Mayan artifacts. 10 It is the purpose of this report to explore the binding of indigo to palygorskite at two compositions (6% wt and 16% wt) and three preparation times (3,6, and 9 h). The conversion of the mixtures of organic and palygorskite to the organic/inorganic complex occurs at 170°C in air.…”
Section: F S Manciu Et Almentioning
confidence: 99%
“…Heating the dye/palygorskite mixture plays a fundamental role in the manufacture of the pigment, since the unheated mixture does not exhibit the chemical stability of Maya Blue. 4,6 The most prevalent hypothesis states that as a result of the heating process, water molecules are eliminated from the entrances of the channels of fibrous palygorskite, and the dye molecules enter into these open channels. 2,4,5 The formation of H-bonds between the indigo carbonyl group and the nearest structural water was suggested as the cause of anchoring the dye inside the clay structure, and the justification for the pigment stability.…”
Section: Introductionmentioning
confidence: 99%
“…Production of Maya Blue in the pre-Colombian MesoAmerica constitutes another example of the know-how of the ancient people 5,6 . In the 60s, the composition of this pigment was elucidated and the durability of Maya Blue was imparted to the association of indigo heat-treated with fibrous clays (palygorskite and sepiolite) 7 . The exceptional chemical stability of Maya Blue is shown by the persistence of the blue colour in acid and oxidising conditions 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…A fim de avaliar a estabilidade química dos materiais híbridos recém-sintetizados utilizou um método de Van Ohphen, com pequenas adaptações [8] . Esse método tem com objetivo a distinção de originalidade do pigmento Azul Maya a partir de outros pigmentos semelhantes.…”
Section: Congo (B)unclassified
“…Uma das principais características desse material é promover uma maior estabilidade das moléculas do corante índigo que são introduzidas nos canais nanométricos da paligorsquita, as quais resistem à ataques com soluções ácidas e/ou alcalinas diluídas, tratamento com solventes e exposição intensa à luz [8,9] . Essas características fizeram com que pinturas utilizando o pigmento Azul Maya resistissem às imtempéries por mais de 1200 anos.…”
Section: Introductionunclassified